Nazariah binti Osman1, Muhammad Muda2, Isah Shehu Mohammed*3 - Juritah Misman, Muhammad Taufik Md Sharipp, S. Salahudin Suyurno, Nik Narimah Nik Abdullah, Chairozila Mohd. Shamsudin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
With the current situation of Covid19 outbreaks and the execution of lockdowns and social restrictions and distancing, people are turning to the use of smart technologies to communicate and perform daily activities. In fact, current education scenario during Covid19 has increased the need to use new media in the teaching and learning processes. In terms of being a good user of this technology, Muslims must advocate to the principles of upholding knowledge and guidance from truthful sources of knowledge such as the Quran and Hadith to avoid becoming deviant users of the new media. The main objective of this paper is to present the Islamic perspectives in terms of the ethics of using the new media in education during covid19. This concept paper analyses data extracted from referencing secondary sources such as academic journal articles, scholarly books and online newspaper articles to understand new media and the current online distance learning situations taking place during Covid19 phenomena. These guidelines would contribute towards aiding teachers and students to have an increase of knowledge and awareness towards the usage of new media as tools during the distance learning transformation while facing the hurdles of life-long learning in Covid19 situations.